2021
DOI: 10.3389/fpls.2021.748242
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Sultr Genes in Malus domestica and Low Sulfur-Induced MhSultr3;1a to Increase Cysteine-Improving Growth

Abstract: Sulfur is an essential nutrient for plant growth and development. Sulfate transporters (Sultrs) are critical for sulfate (SO42-) uptake from the soil by the roots in higher plants. However, knowledge about Sultrs in apples (Malus domestica) is scarce. Here, nine putative MdSultrs were identified and classified into two groups according to the their phylogenetic relationships, gene structures, and conserved motifs. Various cis-regulatory elements related to abiotic stress and plant hormone responsiveness were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Due to the important role of sulfate in plants, SULTRs in several plant species have been studied. For instance, genomes of higher plants like Arabidopsis thaliana, and rice (12 SULTRs), wheat (11 SULTRs), sorghum (10 SULTRs), and apple (9 SULTRs) have been identified [11][12][13][14]. In this study, we identified and characterized 36 and 45 putative SULTR genes in the genome of C. sativa, and B. napus, respectively (Table S1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the important role of sulfate in plants, SULTRs in several plant species have been studied. For instance, genomes of higher plants like Arabidopsis thaliana, and rice (12 SULTRs), wheat (11 SULTRs), sorghum (10 SULTRs), and apple (9 SULTRs) have been identified [11][12][13][14]. In this study, we identified and characterized 36 and 45 putative SULTR genes in the genome of C. sativa, and B. napus, respectively (Table S1).…”
Section: Discussionmentioning
confidence: 97%
“…SULTRs are characterized by 12 transmembrane domains (TMDs) and an AntiSigma factor antagonist (STAS) domain at C-terminus, which is critical for sulfate transporter activity [10]. Genomes of higher plants like Arabidopsis thaliana, rice, wheat, sorghum, and apple were reported to have 12, 12, 11, 10, and 9 SULTR genes, respectively [11][12][13][14]. The SULTR family is well characterized in Arabidopsis, and based on their sequence resemblance, function, and location, the sulfate transporters can be divided into four main groups.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role of sulfate in plants, the SULTRs in several plant species have been studied. For instance, the genomes of higher plants, such as Arabidopsis thaliana , rice (12 SULTRs ), wheat (11 SULTRs ), sorghum (10 SULTRs ), and apple (9 SULTRs ), have been identified [ 11 , 12 , 13 , 14 ]. In this study, we identified and characterized 36 and 45 putative SULTR genes in the genomes of C. sativa and B. napus , respectively ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…SULTRs are characterized by 12 transmembrane domains (TMDs) and an anti-sigma factor antagonist (STAS) domain at the C-terminus, which is critical for sulfate transporter activity [ 10 ]. The genomes of higher plants, such as Arabidopsis thaliana , rice, wheat, sorghum, and apple, have been reported to have 12, 12, 11, 10, and 9 SULTR genes, respectively [ 11 , 12 , 13 , 14 ]. The SULTR family has been well characterized in Arabidopsis , and sulfate transporters can be divided into four main groups based on their sequence resemblance, function, and location.…”
Section: Introductionmentioning
confidence: 99%
“…The SULTR protein is characterized by a sulfate transport anti-sigma (STAS) domain at the C-terminus and a sulfur transport domain at the N-terminus, complemented by 12 transmembrane domains (TMDs) [6]. This protein has undergone comprehensive characterization across diverse plant species, including Arabidopsis [7], sorghum [8], wheat [9], apple [10], Lathyrus sativus [11], Camellia sinensis [12], barley [13], maize [14], tomato [15], radish [16], and others, wherein the SULTR genes have been successfully cloned. Group I of the SULTR genes functioned as a high-affinity transporter responsible for sulfate absorption, primarily expressed in substantial quantities in the roots [17,18].…”
Section: Introductionmentioning
confidence: 99%